Being(s) framed: The means and ends of framing environmental migrants. (November 2015) - Ransan-Cooper, Hedda; Farbotko, Carol; McNamara, Karen E.; Thornton, Fanny; Chevalier, Emilie
Highlights: Reliance on frame analysis to show how different actors define and shape the boundaries of environmental migration. Four unique framings of the environmental migrant arising in popular, policy and academic debate elaborated: victims, security threats, adaptive agents, and political subjects. A qualitative, interpretative review of academic and grey literature used. Of relevance to policymakers, researchers and civil society groups interested in refining communication and development of policy options to address the complex and diverse needs of existing/potential environmental migrants. Abstract: This paper presents an evolving typology of frames – filters of sense-making – to unpack how actors are interpreting and responding to the issue of environmental migration. We use frame analysis to draw attention to how a variety of actors define the boundaries of environmental migration, both intentionally and unintentionally, and how this generates interpretations and directions for policy action. In particular, we identify and discuss four unique framings of the environmental migrant notable in popular policy and academic debate: victims, security threats, adaptive agents and political subjects. Although not always consistently deployed by the same actors, and often hybridised, we argue that the four framings highlight different political, ideological and practical beliefs associated with particular interests and normative assumptions. The paper uses a qualitative, interpretive approach suited to understanding over-arching, macrocultural frames. We explore how key actors produce, communicate and legitimise each framing, discuss the ramifications of such and highlight major apparent critiques. We conclude that despite the four framings identified by us, scope of debate concerning environmental migration is marked by continued dynamism. Within this context, the frame perspective may stimulate greater reflexivity about assumptions and blindspots about this complex phenomenon to ground debate and action, in an arena that often relies on high-level and abstract language.